Traumatic ulcerative granuloma with stromal eosinophilia, an unusual clinical manifestation in the oral mucosa. Case report - Camila Muñoz-Grez; Constanza Ulloa-Bequer (Universidad de Concepción., 2021)
Introduction: Traumatic ulcerative granuloma with stromal eosinophilia is an uncommon condition of the oral mucosa with a chronic course, usually affecting the tongue. Case Report: Clinically it presents as a chronic ulcer, with raised and indurated borders, rarely presented as a tumor. Histologically it shows a diffuse mixed inflammatory infiltrate, rich in eosinophils. The etiology of this lesion is still unclear; however, chronic irritation from traumatic agents is considered a major initiating factor. In some cases, the presence of CD30+ mononuclear cells within the lesions suggest the possibility of a CD30+ lymphoproliferative disorder. This article presents a case of a traumatic ulcerative granuloma with stromal eosinophilia manifested in a 56-year-old female with a solitary ulcerated tumor inside the right cheek. Conclusion: It was diagnosed based on clinical data and histopathological features. In a brief literature review, the entity has been characterized, analyzing its etiology and nature.